Evaluation of Physical, Genital and Psychiatric Examination Findings in Female Sexual Assault and Sexual Abuse Victims - Duman, İmrehan Bilgehan and Gürpınar, S. Serhat and Yıldız, Abdulkadir (The Bulletin of Legal Medicine, 2023)
Objective: It was aimed to reveal the limitations of different structural features of hymen in determining whether there is a sexual intercourse or vaginal sexual assault/abuse and the importance of the other physical examination findings of the genital region, general physical examination and psychological examination findings on creating idea about whether the incident has happened or not, while evaluating this issue. Methods: Between January 1, 2016 and December 31, 2018, 121 cases of sexual abuse and sexual assault which were examined. Results: The rate of detecting physical findings in the genital area, physical findings other than genital areas were determined as 8.3%, 28.9%, respectively, and also a psychiatric finding was observed in 47.1% of cases. The risk of developing psychiatric symptoms is 3.8 times higher in the group with the claim compared to the group without penetration claim, and according to the results of the genital examination, it was found 8.2 times higher in the group with acute rupture. A statistically significant correlation was found between being exposed to physical violence/threat/forced and the development of psychiatric symptoms. A significant correlation was found between the claim of penetration and the development of psychiatric symptoms. Conclusion: Detailed psychiatric evaluations should be made in each case, and the psychological evidence of sexual assault/abuse should be investigated and this evidence should be included as a result of the report.